2011
DOI: 10.1007/s11130-011-0252-2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Domestic Preparation of Some Potato Products on Acrylamide Content

Abstract: The influence that food heating has on the concentration of acrylamide in home-cooked potato dishes prepared by high-temperature, such as pan-frying, deep-frying, roasting and microwave heating was analyzed. The experiment was performed with commercially available deep-frozen par-fried French fries and deep-frozen par-fried potato products other than French fries (cubes, wedges, noisettes, pancakes). Acrylamide was found in all deep-frozen par-fried French fries and other deep-frozen par-fried potato products … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…One important aspect, which is not in the focus of exposure calculations, is the influence of domestic food preparation on the formation of acrylamide and the resulting exposure. Data about the content of acrylamide in homemade food are scarce and only few papers have been published on this important topic . While in industrial food processing several measures have been taken to mitigate the formation of acrylamide, it is unclear to which extent the knowledge about possible setscrews has reached the consumer.…”
Section: Exposurementioning
confidence: 99%
See 2 more Smart Citations
“…One important aspect, which is not in the focus of exposure calculations, is the influence of domestic food preparation on the formation of acrylamide and the resulting exposure. Data about the content of acrylamide in homemade food are scarce and only few papers have been published on this important topic . While in industrial food processing several measures have been taken to mitigate the formation of acrylamide, it is unclear to which extent the knowledge about possible setscrews has reached the consumer.…”
Section: Exposurementioning
confidence: 99%
“…Many pre‐processed products such as par‐fried potatoes already contain acrylamide, but under home cooking conditions with uncontrolled heating facilities the amounts may remarkable increase. For potato products Michalak et al found an increase of acrylamide from 322 µg/kg before final preparation to 469 and 495 µg/kg for pan frying and deep‐frying, respectively, at 180°C for 3 min and 630 and 725 µg/kg for roasting and microwave, respectively, at 220°C for 10 min. Therefore, one demand of Michalak et al was the need for better temperature controlled domestic ovens.…”
Section: Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…However, the information about the contribution of home-cooking practices to acrylamide exposure is very limited. The impact of different culinary procedures on acrylamide in potato-based products has been reported (Michalak, Gujska, & Klepacka, 2011) but the contribution of the consumer practices has not been considered. Delgado-Andrade, Morales, Seiquer, and Navarro (2010) investigated the acrylamide content in several Spanish dishes.…”
Section: Introductionmentioning
confidence: 99%
“…AA is not only formed in commercially produced food but also in considerable amounts in food prepared in restaurants and in home produced food, especially in fried potato products (Michalak et al, 2011;Sanny et al, 2013; see also Section 4.3.2). In parallel with the increasing knowledge on the formation of AA in food, a number of recommendations for mitigation measures of AA concentration in food have been published by national authorities and the food industry.…”
mentioning
confidence: 99%